ANALISIS NILAI SOSIAL DALAM NOVEL NONIK JAMU KARYA RINA SURYAKUSUMA SEBAGAI REKOMENDASI BAHAN AJAR PADA PEMBELAJARAN SASTRA DI SMA - Sembiring, John Timotius; Pratiwi, Wienike Dinar; Syafroni, Roni Nugraha (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study focuses on the meaning of social values contained in the novel Nonik Jamu by Rina Suryakusuma as a recommendation for teaching materials in literature learning in high school. This study uses a qualitative approach. While the research method in this study is a descriptive method. The data collection technique used in this study is a data collection technique using library techniques and note-taking techniques. The classification of social values of compassion consists of devotion values, mutual assistance values, family values, loyalty values, and caring values. There are 18 quotations of sentences that have aspects of social values of compassion consisting of three quotations of sentences based on one description of an event in the value of devotion, three quotations of sentences on one description of an event in the value of mutual assistance, three quotations of sentences on one event that includes family values, five quotations of sentences on one event that includes loyalty values, and seven quotations of sentences that include caring values. Of the five types of social values of compassion, the value of caring is dominated by the value of caring.